A fuzzy system for evaluating students' project in engineering education - BABA, AHMET FEVZİ (WILEY, 2012)
Fuzzy group decision support system is an approach developed to assess the performance of engineering education students. This approach provides multiple perspectives of different people and prevents subjectivity in the evaluation process. It also enables students to take active roles in the assessment. Hence, unbiased evaluation is aimed to be promoted. The developed software for the specific purpose of this study is user-friendly and has multi-criteria decision dimension. The pedagogical implication and aspect of the study have also been displayed in the case study part. The results of the study reveal that fuzzy logic has been influential in increasing the quality of education facilities, motivation, reliability, consistency, and objectivity of the assessment. (c) 2009 Wiley Periodicals, Inc. Comput Appl Eng Educ 20: 287294, 2012
Keywords: fuzzy logic; multi-decision support system; performance assessment